2007
DOI: 10.1186/1465-9921-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epithelial to mesenchymal transition in airways of a bleomycin induced pulmonary fibrosis model derived from an α-smooth muscle actin-Cre transgenic mouse

Abstract: Background: Epithelial to mesenchymal transition (EMT) in alveolar epithelial cells (AECs) has been widely observed in patients suffering interstitial pulmonary fibrosis. In vitro studies have also demonstrated that AECs could convert into myofibroblasts following exposure to TGF-β1. In this study, we examined whether EMT occurs in bleomycin (BLM) induced pulmonary fibrosis, and the involvement of bronchial epithelial cells (BECs) in the EMT. Using an α-smooth muscle actin-Cre transgenic mouse (α-SMA-Cre/R26R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 26 publications
5
111
0
Order By: Relevance
“…Significantly, this response was largely absent in lung from JNK12/2 mice. The emerging role of EMT in pulmonary fibrosis has recently been suggested (69,70), and compelling observations that EMT occurs in the bleomycin model of fibrosis that were based upon lineage tracing have been published (71). However, recent studies have failed to support a role for EMT in IPF or the bleomycin model of fibrosis (72).…”
Section: Discussionmentioning
confidence: 98%
“…Significantly, this response was largely absent in lung from JNK12/2 mice. The emerging role of EMT in pulmonary fibrosis has recently been suggested (69,70), and compelling observations that EMT occurs in the bleomycin model of fibrosis that were based upon lineage tracing have been published (71). However, recent studies have failed to support a role for EMT in IPF or the bleomycin model of fibrosis (72).…”
Section: Discussionmentioning
confidence: 98%
“…Briefly, two loxP sites were inserted at each end of the first exon of the Mypt1 gene, and the resultant Mypt1 flox/flox mice were crossed with transgenic mice with Cre expression driven by a smooth muscle ␣-actin promoter (Mypt1 flox/flox : SMA-Cre mice, MYPT1 SMKO ) (28). The littermates of the Mypt1 flox/flox/ϩ :SMA-Cre mice were used as a control (both male and female mice of 4ϳ60 weeks old).…”
Section: Establishment Of Mypt1mentioning
confidence: 99%
“…Although little is known about how the alveolar epithelium is injured, the ensuing fibrotic response is associated with unrestrained accumulation of fibroblasts and myofibroblasts that synthesize and deposit collagen fibrils within fibroblast foci located in the pulmonary parenchyma (2,3). Recent studies have suggested that pulmonary fibroblasts arise by several routes including increased migration and proliferation of resident pulmonary fibroblasts, mesenchymal transition of the alveolar epithelium, and recruitment of bone marrow-derived progenitor cells (4)(5)(6)(7). In the presence of TGF-b and other agonists, resident fibroblast subsets transdifferentiate into a-smooth muscle actinpositive myofibroblasts (8,9), produce increased amounts of collagen, and, through their contractile activities, distort the parenchymal lung architecture (9,10).…”
mentioning
confidence: 99%